Slackline training (balancing over narrow Nylon ribbons) and balance performance: A meta-analytical review - Donath, L.; Roth, R.; Zahner, L.; Faude, O. (Sports Medicine, 2017)
Background: Adequate static and dynamic balance performance is an important prerequisite during daily and sporting life. Various traditional and innovative balance training concepts have been suggested to improve postural control or neuromuscular fall risk profiles over recent years. Whether slackline training (balancing over narrow nylon ribbons) serves as an appropriate training strategy to improve static and dynamic balance performance is as yet unclear. Objective: The aim was to examine the occurrence and magnitude of effects of slackline training compared with an inactive control condition on static and dynamic balance performance parameters in children, adults and seniors. Data sources: Five biomedical and psychological databases (CINAHL, EMBASE, ISI Web of Knowledge, PubMed, SPORTDiscus) were screened using the following search terms with Boolean conjunctions: (slacklin* OR slack-lin* OR tight rop* OR tightrop* OR Slackline-based OR line-based OR slackrop* OR slack-rop* OR floppy wir* OR rop* balanc* OR ropedanc* OR rope-danc*) Study selection: Randomized and non-randomized controlled trials that applied slackline training as an exercise intervention compared with an inactive control condition focusing on static and dynamic balance performance (perturbed and non-perturbed single leg stance) in healthy children, adults and seniors were screened for eligibility. Data extraction: Eligibility and study quality [Physiotherapy Evidence Database (PEDro) scale] were independently assessed by two researchers. Standardized mean differences (SMDs) calculated as weighted Hedges` g served as main outcomes in order to compare slackline training versus inactive control on slackline standing as well as dynamic and static balance performance parameters. Statistical analyses were conducted using a random-effects, inverse-variance model. Results: Eight trials (mean PEDro score 6.5 ± 0.9) with 204 healthy participants were included. Of the included subjects, 35 % were children or adolescents, 39 % were adults and 26 % were seniors. Slackline training varied from 4 to 6 weeks with 16 ± 7 training sessions on average, ranging from 8 to 28 sessions. Mean overall slackline training covered 380 ± 128 min. Very large task-specific effects in favor of slackline training compared with the inactive control condition were found for slackline standing time {SMD 4.63 [95 % confidence interval (CI) 3.67-5.59], p < 0.001}. Small and moderate pooled transfer effects were observed for dynamic [SMD 0.52 (95 % CI 0.08-0.96), p = 0.02] and static [SMD 0.30 (95 % CI -0.03 to 0.64), p = 0.07] standing balance performance, respectively. Conclusions: Slackline training mainly revealed meaningful task-specific training effects in balance performance tasks that are closely related to the training content, such as slackline standing time and dynamic standing balance. Transfer effects to static and dynamic standing balance performance tasks are limited. As a consequence, slackline devices should be embedded into a challenging and multimodal balance training program and not used as the sole form of training.